PERBANDINGAN PERSEDIAAN BAHAN BAKU DAN BAHAN TAMBAHAN DENGAN METODE ECONOMICAL ORDER QUANTITY PADA PT. JAPFA COMFEED INDONESIA tbk - putri suwarni (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
The results of initial observation at PT. Japfa Comfeed Indonesia obtained data that the company always buys raw materials and auxiliary materials in large quantities and does not pay any attention to reorder in order not to run out of stock of raw materials and additives. To describe and analyze the optimal inventory and minimize the total cost of raw material inventory and additive then conducted qualitative research extrapolation (descriptive) by using EOQ method. The object of this research is the amount of raw material inventory and additional material at PT. Japfa Comfeed Indonesia. The raw material in this research is Brand Pollard, Stone Flour. Additional materials include Termin and Palm Oil. The results obtained with the optimal buyer Brand Pollard in 2016 amounted to 1,185,906 kg and in 2016 amounted to 1,215,745 kg. The purchase of Stone Flour 2016 is 677,847 kg and in 2016 it is 711,395 kg. The purchase of Palm Oil and Terminal in 2015 amounted to 282,281 liters and 212,776.8 liters respectively. Brand Pollard reorder point in 2015 and 2016 amounted to 139.968 kg Purchase of Stone Flour in 2015 and 2016 amounted to 38,166 kg. Palm Oil and terminal purchases in 2015 and 2016 amounted to 19,200 liters and 16,440 liters respectively. Financially, the company can make inventory cost savings up to Rp 88,043,000.00. The conclusion of this research is the determination of the amount of raw material inventory and additional material with EOQ method which more efficient compared with company policy. The optimal inventory and total inventory cost savings can be obtained by EOQ method so that the company can obtain maximum profit. Suggestion related to this research is company must evaluate applied policy and apply EOQ method in management of raw material inventory and additional material to get maximum profit. Keywords : Raw Material Inventory, Supplementary Material Inventory, Total Quantity Economica